Loneliness among elderly people as a public health threat - Susło, Anna; Mizia, Sylwia; Pochybełko, Ewa; Horoch-Łyszczarek, Ewa (Family Medicine & Primary Care Review, 2023)
Each day, primary care physicians see many lonely elderly people with multiple complaints, who sometimes can be labelled “over-demanding” or even “abusing health services”; in fact, this phenomenon results from general deficiencies and insufficiency in social support. A literature review has been carried out in order to identify the characteristics of loneliness in people aged sixty years and older, and its health-related consequences. Loneliness causes sensory deprivation and emotional starvation, which translate into a subjective feeling of discomfort and distress, as well as into objective behavioral chang-es. Loneliness is a prognostic factor for worsened health and cognitive status in the elderly. The limited ability of elderly people to take care of themselves as a result of deterioration in health does not itself lead to loneliness and abandonment if the social support system is not deficient. Paradoxically, policies intended to protect the elderly often result in negative phenomena, such as actual discrimination justified on the basis of paternalistic and generalizing assumptions. Loneliness among elderly people is becoming a serious public health problem in modern atomized, ageing societies. This thus demands urgent action from the Polish state, aimed at providing the elderly with organized social support in order to adequately protect their health and well-being. Cur-rently, different levels of the health system, including primary care physicians, are forced to deal with the increasing fallout of loneliness, which presents in the form of physical and mental illnesses, as well as psychosomatic ailments.